Black-necked Swan Cygnus melancoryphus and Coscoroba Swan Coscoroba coscoroba in a wetland in Uruguay - Vaz-Ferreira, R; Rilla, F (Wildfowl, 2013)
Study of the distribution and numbers of the Black-necked Swan and Coscoroba Swan showsÂ maximum numbers in the southeast area of the country where they inhabit shallow areas of coastalÂ lagoons; in particular Laguna de Rocha, a shallow logoon (0.58 m in medium depth) which hasÂ intermittent connections with the sea, sometimes man-made.Â In this lagoon up to 7,000-10,000 Black-necked Swans and up to about 400 Coscoroba SwansÂ were counted in some occasions.Â During October 1988 to February 1989 the mouth o f the Rocha lagoon was not open to the seaÂ and its water level rose about one metre. This coincided with an exceptional drought, which causedÂ dispersion and mortality of the swans inhabiting this lagoon and other wetlands in Uruguay. TheÂ swans dispersed among atypical areas such as dry meadows, estuaries and deep waters, the saltyÂ Rio de la Plata and even the waters of the Atlantic to 2km offshore. Due to this dispersion andÂ mortality the number of swans in the Laguna de Rocha has decreased by more than 90% comparedÂ to the situation in 1987.